Liver Transplantation for Acute Liver Injury in Asians Is More Likely Due to Herbal and Dietary Supplements. Issue 2 (13th December 2021) - Kesar, Varun; Channen, Lindsey; Masood, Umair; Grewal, Priya; Ahmad, Jawad; Roth, Nitzan C.; Odin, Joseph A.
Abstract : Drug‐induced liver injury (DILI) due to medications and herbal and dietary supplements (HDSs) is a major cause of acute liver injury leading to liver transplantation (LT). This study used United Network for Organ Sharing LT data to analyze severe HDS‐induced acute liver injury in the United States. By convention, patients with acute DILI are listed as "Acute Hepatic Necrosis" (AHN) under the subheading "AHN: Drug Other Specify." All patients waitlisted from 1994 to 2020 were divided into 3 subgroups: "HDS DILI, " "Non‐HDS DILI, " and "AHN: unknown drug." Analyses were performed to identify epidemiologic differences between patients with HDS DILI and non‐HDS DILI. A subanalysis was performed for transplanted patients, including longitudinal changes. Of 1875 patients waitlisted for LT, 736 (39.2%) underwent LT. The proportion of Asian patients in the HDS DILI group was significantly higher compared with that in the non‐HDS DILI group (17.4% versus 3.8%; P < 0.001). Excluding acetaminophen cases, the proportion of Black patients in the HDS DILI versus non‐HDS group was significantly lower (8.7% versus 25.3%; P < 0.001). Waitlisted patients with HDS DILI were significantly older (median age, 38 years for HDS DILI versus 31 years for non‐HDS DILI; P = 0.03). Lastly, the number of patients requiring LT due to HDS DILI increased significantly over time with more than 70% of cases occurring in the last 10 years (2010‐2020) compared with the prior 15 years (1994‐2009; P trend = 0.001). Ethnicity may help in identifying the cause of severe acute DILI, a growing problem as more patients experiment with HDS.